Does the Zero Lower Bound affect Euro Area productivity?: a case study - Moreira, Duarte Nuno Graça (2020)
The main research question associated with this case study is to contribute modestly to the discussion of the relationship between Zero Lower Bound (ZLB) framework and Productivity of the Euro Area, Germany and the GIIPS. The relationship between ZLB and Unit Labor Costs is also analyzed. The series analyzed correspond to the period from the first quarter of 2000 to the third quarter of 2018. The purpose of choosing this period is to maximize the quality of the analysis by addressing multiple stages of the global business cycles. To put this analysis into practice, the Vector Error Correction Model (VECM) was applied and the Granger Causality was analyzed. It is possible to conclude that only in Portugal does the ZLB affect Productivity and that the ZLB affect unit labor costs in Portugal and Spain exclusively.